Transformation to small cell lung cancer after first-line afatinib treatment. (2018) - Shiroyama, Takayuki; Nasu, Shingo; Tanaka, Ayako; Takata, So; Masuhiro, Kentaro; Takada, Hiromune; Morita, Satomu; Morishita, Naoko; Suzuki, Hidekazu; Okamoto, Norio; Kawahara, Kunimitsu; Hirashima, Tomonori
Abstract: Acquiring resistance to epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) is inevitable. Transformation to small cell lung cancer (SCLC) is reported as a possible mechanism of this acquired resistance. We describe the case of a 35-year-old man with lung adenocarcinoma harboring EGFR exon 19 deletion. After 7 months of successful treatment with afatinib, he experienced relapse and rebiopsy revealed SCLC with EGFR exon 19 deletion. Tumor marker tests at this point showed normal levels of serum neuron-specific enolase and pro-gastrin releasing peptide. Our case highlights the importance of rebiopsy for revealing SCLC transformation, a potential mechanism of acquired resistance to afatinib as with other EGFR-TKIs, and normal-range values of tumor markers for SCLC cannot exclude the possibility of SCLC transformation.